2000
DOI: 10.1021/np000020e
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Agents. 203. Carbazole Alkaloid Murrayaquinone A and Related Synthetic Carbazolequinones as Cytotoxic Agents

Abstract: Murrayaquinone A (1) and murrayafoline A (3), isolated from the root bark of Murraya euchrestifolia, were identified as cytotoxic compounds. Murrayaquinone A (1) demonstrated significant cytotoxicity against SK-MEL-5 and Colo-205 cells, with ED(50) values of 2.58 and 3.85 microg/mL, respectively. In contrast, murrayafoline A (3) exhibited marginal or weak cytotoxicity against SK-MEL-5, Colo-205, HCT-8, KB, and A-549 tumor cell lines, with ED(50) values ranging from 5.31 to 7.52 microg/mL. In total, 20 carbazol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
100
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(100 citation statements)
references
References 18 publications
(61 reference statements)
0
100
0
Order By: Relevance
“…Murrayaquinone and murrayafoline-A from the root of M. euchrestifolia (Furukawa et al, 1985) have been found to have weak but fairly selective cytotoxic activity against a panel of about 60 tumour cell lines (Itoigawa et al, 2000). Itoigawa et al (2000) also found that several other natural and synthetic carbazoles had more selective cytotoxicities.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Murrayaquinone and murrayafoline-A from the root of M. euchrestifolia (Furukawa et al, 1985) have been found to have weak but fairly selective cytotoxic activity against a panel of about 60 tumour cell lines (Itoigawa et al, 2000). Itoigawa et al (2000) also found that several other natural and synthetic carbazoles had more selective cytotoxicities.…”
Section: Resultsmentioning
confidence: 99%
“…Murrayaquinone and murrayafoline-A from the root of M. euchrestifolia (Furukawa et al, 1985) have been found to have weak but fairly selective cytotoxic activity against a panel of about 60 tumour cell lines (Itoigawa et al, 2000). Itoigawa et al (2000) also found that several other natural and synthetic carbazoles had more selective cytotoxicities. The activities of the carbazole alkaloids from M. koenigii described here would seem to justify some of the folk medicinal uses of the plant, for example in the treatment of diarrhoea, dysentery and against biting insects (Kirtikar et al, 1993;Yusuf et al, 1994).…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that carbazole derivatives exhibit various biological activities such as antitumor (Itoigawa et al, 2000), anti-inflammatory and antimutagenic (Ramsewak et al, 1999). Carbazole derivatives also exhibit electroactivity and luminenscence and are considered to be potential candidates for electronic applications such as colour displays, organic semiconductors, laser and solar cells (Friend et al, 1999;Zhang et al, 2004).…”
Section: Commentmentioning
confidence: 99%
“…A number of natural carbazole alkaloids were recognized to exhibit potential biological activities such as antimicrobial [1,2], anti-HIV [3], anticancer [4,5,6] activities. Among them, several compounds were used as drugs for treatment of cancer [7].…”
Section: Introductionmentioning
confidence: 99%